Aggressive Behavior and Poor Prognosis of Endometrial Stromal Sarcomas With YWHAE-FAM22 Rearrangement Indicate the Clinical Importance to Recognize This Subset. Issue 9 (1st November 2014) - Kruse, Arnold-Jan; Croce, Sabrina; Kruitwagen, Roy F.P.M.; Riedl, Robert G.; Slangen, Brigitte F.M.; Van Gorp, Toon; Van de Vijver, Koen K.
Abstract : Objectives: Although the World Health Organization (WHO) in 2003 defined endometrial stromal sarcomas (ESSs) in general have a good prognosis, considerable differences in clinical behavior and prognosis may exist between different patients with ESS. The ESSs of the type associated with YWHAE-NUTM2 (previously named YWHAE-FAM22 ) fusion have a more aggressive clinical behavior and poorer prognosis than conventional ESS. Recently, the WHO 2014 classification recognizes this subset of ESS as a separate entity and classifies these as high-grade ESSs. Recognition of this subset has therefore an important clinical impact. We performed a review of the literature to delineate the clinicopathologic features of ESS patients with an YWHAE-NUTM2 rearrangement, with the goal to recognize this subset of ESS. Methods: We report a case of a woman with WHO 2014–defined high-grade ESS. Furthermore, published English literature was reviewed for YWHAE-FAM22 ESS and uterus. Results: Twenty patients were identified, with a median age of 50 (range, 28–67) years. There were no clinical features able to recognize YWHAE-NUTM2 ESS. However, they characteristically contain specific histopathological features. Furthermore, YWHAE-NUTM2 ESSs are strongly cyclin D1 positive in contrast to conventional low-grade ESSs. Conclusions: YWHAE-NUTM2 ESSs represent a subset of ESSs with an aggressive clinical behavior and poor prognosis. Specific histopathological features may indicate the presence of YWHAE-NUTM2 rearrangement, which subsequently can be confirmed by cyclin D1 immunostaining.